Construction of cubature formula for double integration with algebraic singularity by spline polynomial - Bichi, Sirajo Lawan; Eshkuvatov, Zainidin K.; Nik Long, Nik Mohd Asri; Ismail, Fudziah (IEEE, 2015)
In this note, singular integration problems of the form Hα (h) = ∫Ω∫ h(x,y)/|-x0|2-α dA, 0 ≤ α ≤ 1, where Ω = [x0,y0] × [b1, b2], x= (x,y) ϵ Ω and fixed point x 0 = (x0,y0) ϵ Ω is considered. The density function h(x, y) is assumed given, continuous and smooth on the rectangle Ω and belong to the class of functions C2,α(Ω). Cubature formula for double integrals with algebraic singularity on a rectangle is constructed using the modified spline function SΩ(P) of type (0, 2). Highly accurate numerical results for the proposed method is given for both tested density function h(x, y) as linear, quadratic and absolute value functions. The results are in line with the theoretical findings.